Reliability of Cardiorespiratory Parameters During Cycling Exercise Performed at the Severe Domain in Active Individuals - Barbosa, Luis F. [UNESP]; Montagnana, Lucas [UNESP]; Denadai, Benedito S. [UNESP]; Greco, Camila C. [UNESP] (Lippincott Williams & Wilkins, 2014)
Barbosa, LF, Montagnana, L, Denadai, BS, and Greco, CC. Reliability of cardiorespiratory parameters during cycling exercise performed at the severe domain in active individuals. J Strength Cond Res 28(4): 976-981, 2014-The purpose of this study was to determine the test-retest reliability of cardiorespiratory parameters during cycling exercise performed at severe domain in active individuals. Thirteen active males (24.5 +/- 4.5 years) performed the following tests: (a) an incremental test to determine V ̇o(2)max and the intensity associated with V ̇o(2)max (IV ̇o(2)max); and (b) 4 repetitions of square-wave transitions from rest to a power corresponding to 95%IV ̇o(2)max to determine the parameters of V ̇o(2) kinetics and time to exhaustion (Tlim). Participants performed only 2 transitions on any given day. The interval between the 2 experimental sessions was 48-72 hours. The intraclass correlation coefficient (ICC) and typical error as the coefficient of variation were used to assess reliability. Although the 2 measures of Tlim were moderately related (ICC = 0.78; p < 0.01), Tlim from the second session (545.2 +/- 103.1 seconds) was significantly higher than that of the first (492.5 +/- 100.9 seconds; p = 0.02). Moderate to high reliability (ICC = 0.76-0.93) for the amplitudes of the V ̇o(2) kinetics responses was found. Poor reliability, however, was found for time constants and time delays of the V ̇o(2) kinetics responses. Thus, in nonfamiliarized individuals, Tlim shows a relatively low within-subject coefficient of variation. However, the second score in a series of 2 Tlim tests may be significantly greater than the first. We have also demonstrated that the amplitudes of the V ̇o(2) response have significantly moderate to high reliability. The time-based parameters, however, present an important day-to-day intraindividual variation. Therefore, several transitions are recommended to monitoring changes in an individual over any time frame.
Keywords: oxygen uptake kinetics; slow component; time to exhaustion